Survey of vector-borne and nematode parasites involved in the etiology of anemic syndrome in sheep from Southern Brazil - Mongruel, Anna Claudia Baumel; Spanhol, Viviane Campos; Valente, Jessica Damiana Marinho; Porto, Petrônio Pinheiro; Ogawa, Liza; Otomura, Flávio Haragushiku; Marquez, Ellen de Souza; André, Marcos Rogério [UNESP]; Vieira, Thállitha Samih Wischral Jayme; Vieira, Rafael Felipe da Costa (FapUNIFESP (SciELO), 2020)
Although anemia has been historically linked to Haemonchus contortus infection, other infectious agents, such as hemotropic mycoplasmas and tick-borne disease pathogens, may also lead to anemic crisis in sheep. This study has aimed to investigate infections related to anemia in a sheep herd from Bandeirantes City, Paraná State, southern Brazil. Seven out of forty-two (16.6%; 95% CI: 8.32-30.6%) sheep were positive for hemoplasmas by a PCR targeting the 16S rRNA gene and all tested negative for A. marginale/A. ovis and Babesia/Theileria spp. by PCR based on msp4 and 18S rRNA genes, respectively. Two (4.7%; 95% CI: 1.32-15.79%) animals were infested with Rhipicephalus microplus ticks. Fecal egg counting was performed in 38 sheep and 24 (63.15%; 95% CI: 47.2-76.6%) presented > 500 eggs per gram. Phylogenetic analysis of partial sequences of the detected hemotropic Mycoplasma sp. 16S and 23S rRNA genes confirmed that the animals were infected with Mycoplasma ovis. Polymorphism analysis of partial 16S rRNA sequences showed three different genotypes of M. ovis infecting sheep assessed in the present study. Mycoplasma ovis and gastrointestinal nematodes occurs in sheep from the northern region of Paraná State.